Daughter of Cana [large type] - Hunt, Angela Elwell, 1957- (Hunt, Angela Elwell, 1957- Jerusalem Road, 2020)
"Thomas and Tasmin, twin siblings hired to oversee a wedding feast in Cana, worry when the host runs out of wine . . . until a guest tells Tasmin to have the servants fill the pitchers by the gate with water from the cistern. Reluctantly, she obeys and is amazed when rainwater turns into the finest wine ever tasted in Cana. When Thomas impulsively decides to follow the teacher from Nazareth, he and Tasmin argue--since the twins have been together since the womb, Tasmin can't accept losing her brother to some magician-prophet. Aided by Jude, younger brother to Jesus of Nazareth, she decides to follow the Nazarene's group and do whatever she must to mend the fractured relationship and bring her brother home."--